Behaviour and physiology assessment of false gharial [Tomistoma schlegelii (Müller, 1838)] in captivity in Peninsular Malaysia - Ab Latip, Mohd Qayyum (2017)
Tomistoma schlegelii or the “False Gharial” is one of the crocodile species in Malaysia. It is one of the largest extant crocodilians, restricted to Southeast Asia. Investigation of old localities show that the species may still be present, but the basic ecology and behaviour of this species still remain undocumented. Captive False Gharial of 2 cohorts, adult and juvenile, were restrained and sampled from the Semi wild captive environment, National zoo and Taiping zoo. The research has 3 objectives. (i) to identify the bacterial flora in cloacal cavities of captive and semi-wild False Gharial in Peninsular Malaysia, (ii) to determine the blood profile of captive and semi-wild False Gharial in Peninsular Malaysia and (iii) to determine nesting behaviour and ecology of False Gharial in natural pond. Bacterial cultures were done from cloacal swabs collected from 10 samples of captive False Gharial. 13 species of bacteria were cultured from 42 isolates. Each individual crocodiles yielded 3 to 5 bacterial species and no crocodiles were found to yield a single species. The most commonly isolated bacteria were Proteus vulgaris and Salmonella spp. and all the bacteria were gram negative. Most of the genera belong to the family Enterobacteriaceae. Blood was collected from the lateral coccygeal vein and used for identification of the wide range of haematological and biochemical parameters as a preliminary study on this species. The values were compared between the sexes, ages and location of False Gharial. Comparison was also done with other species in the same family Gavialis gangeticus, Indian Gharial, False Gharial in the previous study and Crocodylus porosus, Salt-water Crocodile. Peripheral blood cells of False Gharial showed erythrocyte cell which is an oval in shape and with centrally located prominent round or oval nucleus. Erythrocyte and haemoglobin count in False Gharial that placed at zoos had significantly lower mean than False Gharial at semi wild captive environment. The mean of white blood cell was significantly lower in Flase Gharial that kept at zoos than semi wild captive environment. The average most abundant leukocyte type in False Gharial was heterophils (56.90%), followed by lymphocytes (17.60%), monocytes (10.60%), eosinophils (9.70%), basophils (5.40%) and thrombocytes (3.70%). Serum biochemistry showed total protein, albumin, potassium, bilirubin, creatine kinase, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were higher in Flase Gharial at zoos than False Gharial at semi wild captive environment. For the nesting behavioural ecology of captive False Gharials, observation were conducted in semi wild captive environment because the natural substrate of the captive pond simulates the wild environment. Throughout the study, one female individual laid eggs twice, 34 eggs and 28 eggs per clutch, respectively, which is in June 2013 and June 2014. Unfortunately all the eggs were infertile. This species build the nest mounds from sand, soil, dried leaves and twigs. The composition ratio of vegetation matters to soil is 60:40, while the temperature range that was recorded is between 29°C – 32°C.